The EDPITAF Library development program a case study - Ruiz, Ma. Socorro D. (Institute of Library Science, University of the Philippines Diliman, 1977)
This special problem is a case study on the operations of the library of the Educational Development Projects Implementing Task Force (EDPITAF). It has three objectives: (1) to study the EDPITAF Library with the motive of making it a potent member of the organization; (2) to lend librarians of emerging libraries firsthand information on the development of a library; and (3) to contribute to the meager literature on library development.